Waste What? A game to communicate about local circular economy practices - Scholz, Johannes Roland; Ordonez, Isabel; Rotter, Vera Susanne (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Waste What? is a card game, intended to communicate about linear economy while highlighting sustainable alternatives of local circular economy (CE) practices offered by grassroot initiatives. The objective of this article is to present the applied co-creative game development process and to show identified CE enablers included in the game. Based on the results, lessons learned and recommendations for future projects are formulated. The project that developed Waste What? used a co-creative development process with four phases: 1. Field Trips: That collected perspectives, insights, and impressions from local CE-Stakeholders. 2. Prototyping: Developed the game concept based on observations. 3. Testing & Design: Prototypes are developed into the final game by including the perspectives of stakeholders in testing sessions. 4. Dissemination and Documentation: The game was documented and published with an open-source license and disseminated at events. With an individual design of 110 cards, a game board, chips, and a manual, Waste What? communicates an experience of involvement in local CE- practices. In the game, players from two teams take the perspective of CE-initiatives. They are active in the re-use of items of the categories: Textiles, Electronics, Food, Furniture, Construction Materials and Bicycles. Players have several options, including selling, donating, storing, combining or incinerating items. The game communicates observed CE-enablers connected to people, items, and infrastructure. The study concludes that CE-games can communicate principles and people are interested in the approach. However, it is recommended to tailor games to specific target groups and plan extensive dissemination efforts to maximize its impact.